A bird-eye view of diaphragmatic endometriosis: current practices and future perspectives - Naem, Antoine; Roman, Horace; Martin, Dan C.; Krentel, Harald (Frontiers in Medicine, 2024)
Diaphragmatic endometriosis is one of the most common localization of extra-pelvic endometriosis and may cause debilitating symptoms such as cyclic shoulder pain, right upper abdominal pain, and right-sided chest pain. Diaphragmatic endometriosis may also be asymptomatic. The exact mechanisms by which diaphragmatic endometriosis originates are unknown. The high correlation between severe pelvic endometriosis and diaphragmatic endometriosis suggests that the latter originates from endometriotic cells that reach the upper abdomen by circulating with the peritoneal fluid current. Robust evidence regarding the preoperative diagnosis and optimal management of diaphragmatic endometriosis is lacking. Most reports rely on Magnetic Resonance Imaging (MRI) for the radiologic diagnosis of diaphragmatic endometriosis. Although its sensitivity ranged between 78-83%, MRI was found to underestimate the extent of diaphragmatic endometriosis in comparison with the surgical findings. Accumulating evidence indicates that asymptomatic diaphragmatic endometriosis is very unlikely to progress, and therefore, could be left in situ when incidentally found. The efficiency of ablative and excisional approaches for symptomatic endometriosis has not been assessed thoroughly to date. In addition, it is unclear whether combining the laparoscopic approach with video-assisted thoracoscopy (VATS) may result in an optimized result. This gap exists due to the lack of data about the association between diaphragmatic and thoracic endometriosis. In this review, we aimed to provide a state of the art description of the current knowledge and gaps about the pathogenesis, diagnostics, and treatment modalities of diaphragmatic endometriosis.